Study of Physicochemical Parameters and Organochlorine Pesticide Residues of Water from Gusau Dam and Water from Treatment Board in Gusau, Zamfara State, Nigeria - Momoh, Shaibu; Samila .A.ABDULLAHI (International Journal of Scientific Research and Innovative Studies, 2022)
In this study, effect of conventional water treatment on the removal of organochlorine pesticide residues OCP was evaluated. Water samples were collected from Gusau Dam and Gusau water board. The two samples were analyzed for the present of OCP using QuECHERS and GC-ECD for samples preparation and analysis respectively. Twenty organochlorine pesticide standard were used and only five organochlorine pesticide residues were detected in the water samples from Dam namely; alpha lindane, endosulfan ether, isodrine, heptachlor epoxide and DDMU with concentration 0.0250 mg/L, 0.0270 mg/L, 0.0141 mg/L, 0.0003 mg/L, 0.0016 mg/L respectively. Only two OCP residues are detected in treated water samples namely; lindane and endosulfan with concentration 0.0001 mg/L and 0.0012 respectively. The entire organochlorine pesticide residue detected in dam water samples are within the maximum residual limit (MRL) except alpha lindane and endosulfan ether that are little higher than 0.02 mg/L of MRL while that of treated water are below MRL. Statistical analysis (t-test) of physicochemical shows that, there is no significance difference between the physicochemical parameters of water samples from Dam and water board. The presence of organochlorine pesticides residues in the dam shows that farmers are still using these banned organochlorine pesticides for pest control; therefore, there is need for routine monitoring and the use of effective absorbent for water treatment in order to minimize health risk to human.